2021
DOI: 10.1523/jneurosci.2038-20.2021
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Tracking Age Differences in Neural Distinctiveness across Representational Levels

Abstract: The distinctiveness of neural information representation is crucial for successful memory performance but declines with advancing age. Computational models implicate age-related neural dedifferentiation on the level of item representations, but previous studies mostly focused on age differences of categorical information representation in higher-order visual regions. In an age-comparative fMRI study, we combined univariate analyses and whole-brain searchlight pattern similarity analyses to elucidate age differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 93 publications
7
44
3
Order By: Relevance
“…Koen et al, (2019) found evidence that neural attenuation drove their findings of reduced neural distinctiveness in older adults. On the other hand, Kobelt et al, (2021) found increased neural activation in response to non-preferred stimuli in older adults, with no age differences in activation to preferred stimuli, supporting the neural broadening hypothesis. Park et al, (2012) provided support for both, finding evidence of neural broadening in the FFA and neural attenuation in the extended face network.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Koen et al, (2019) found evidence that neural attenuation drove their findings of reduced neural distinctiveness in older adults. On the other hand, Kobelt et al, (2021) found increased neural activation in response to non-preferred stimuli in older adults, with no age differences in activation to preferred stimuli, supporting the neural broadening hypothesis. Park et al, (2012) provided support for both, finding evidence of neural broadening in the FFA and neural attenuation in the extended face network.…”
Section: Introductionsupporting
confidence: 56%
“…Several other studies have used MVPA to replicate these findings of reduced age-related dedifferentiation at the level of category representations (Chamberlain et al, 2021; J. Park, Carp, Hebrank, Park, & Polk, 2010) and recently Kobelt et al, (2021) found that item-level distinctiveness was also reduced in older adults.…”
Section: Introductionmentioning
confidence: 75%
“…Third, due to the of current study design, every item viewed during encoding is its own perceptual category. We are therefore unable to calculate neural distinctiveness during encoding to use as a baseline neural similarity measure, as recent studies have with face and house categories of visual stimuli (Hill et al, 2021;Kobelt et al, 2021). However, we contend that global ERS is an appropriate and theoretically meaningful baseline assessment of recapitulation between younger and older adults when assessing single-item ERS.…”
Section: Limitations and Future Directionsmentioning
confidence: 88%
“…In line with these models, dedifferentiation has repeatedly been observed in older adults (OA) at the behavioral and neural levels (Park et al, 2004;Carp, Park, Hebrank, Park, & Polk, 2011;Koch et al, 2020;Kobelt, Sommer, Keresztes, linked to decreased memory performance (Koen, Hauck, & Rugg, 2019;Sommer et al, 2019;St-Laurent, Abdi, Bondad, & Buchsbaum, 2014), establishing an explanatory link between DA, neural representations and cognitive aging. These roles of DA in spatial navigation and aging might contribute to the pronounced decline in spatial cognition with age (Moffat, 2009;Lester, Moffat, Wiener, Barnes, & Wolbers, 2017;Wolbers, Dudchenko, & Wood, 2014;Schuck, Doeller, Polk, Lindenberger, & Li, 2015), and to the neural dedifferentiation of direction-selective (Koch et al, 2020) and hippocampal signals (Schuck et al, 2015) in the aging brain.…”
Section: Introductionmentioning
confidence: 91%